Importance of Three-Dimensional Evaluation of Surgical Transepicondylar Axis in Total Knee Arthroplasty - Ohmori, Takaaki; Kabata, Tamon; Kajino, Yoshitomo; Inoue, Daisuke; Ueno, Takuro; Taga, Tadashi; Yamamoto, Takashi; Takagi, Tomoharu; Yoshitani, Junya; Ueoka, Ken; Yamamuro, Yuki; Tsuchiya, Hiroyuki (The Journal of Knee Surgery, 2020)
In total knee arthroplasty, the surgical transepicondylar axis (SEA) is one of the most reliable rotation axes for stabilizing of the patellofemoral joint. The SEA is identified with reference to the lateral epicondyle and the medial sulcus of the medial epicondyle. However, these two structures rarely appear on the same plane on computed tomography (CT), and it is necessary to take two points in separate images. Many surgeons measure the SEA on the same image (pseudo SEA) instead. We aimed to determine the difference between true SEAs and pseudo SEAs. A total of 31 normal knees and 24 varus knees were included in this study. Three-dimensional (3D) models of the femur were reconstructed from CT images, and a reconstructed plane was made using the International Society of Biomechanics coordinate system. Pseudo SEAs drawn in the plane passing through the lateral epicondyle and medial sulcus were defined as l-SEA and m-SEA, respectively. L-SEA, m-SEA, true SEA, and posterior condylar axis (PCA) were projected onto the International Society of Biomechanics coordinate plane and, “p l-SEA,” “p m-SEA,” “p true SEA,” and “p PCA” were obtained. The true SEA angle was defined as the angle between p true SEA and p PCA. The l-SEA angle or m-SEA angle was defined as the angle between the p l-SEA or p m-SEA and p PCA, respectively. There were no statistically significant differences between true SEA angle (2.64 ± 2.01 degrees) and pseudo SEA angle (l-SEA angle: 2.74 ± 2.07 degrees, m-SEA: 2.54 ± 2.19 degrees). Conversely, 12 knees in the normal group and 2 knees in the varus group had differences of more than 1 degree (p = 0.01). Among them, 6 knees in the normal group and 0 knees in the varus group had a difference of 2 degrees or more (p = 0.03). In most cases, pseudo SEA can be substituted for true SEA.
Keywords: total knee arthroplasty; true surgical transepicondylar axis; pseudo surgical transepicondylar axis